A coupling method incorporating digital image processing and discrete element method for modeling of geomaterials. Issue 1 (5th March 2018) - Meng, Qingxiang; Wang, Huanling; Xu, Weiya; Zhang, Qiang
Abstract : Purpose: This paper aims to present a digital image processing (DIP)-based discrete element method (DEM) for the analysis of heterogeneous geomaterials. Taking a soil and rock mixture as an example, the direct shear test is used to illustrate the application of this method. The numerical result is validated by the laboratory experiment and implies its feasibility in the analysis of heterogeneous geomaterials. Design/methodology/approach: This method has two major steps. Based on a modification of the connected-component labeling algorithm, a novel vectorization method, which can transform the digital photos to vectorized geometry automatically, is proposed first. Then, a simple yet effective method for the generation of heterogeneous DEM models is presented using the simulation of simplicity technique. Findings: DIP-DEM method is a feasible approach for the analysis of mechanical behavior of heterogeneous material. For soil and rock mixtures (SRM), the horizantal deformation at peak shear point becomes larger with the normal stress. Compared with pure soil, the rock aggregates mainly improve the friction angle of SRM. Originality/value: As a universal method taking advantage of both DIP and DEM, this method has broad application prospects in related fields.